PENERAPAN PEER COACHING MODEL DALAM PEMBELAJARAN PENJAS UNTUK MENINGKATKAN SELF-REGULATED LEARNING SISWA SMK 3 SELONG - Rizqia Maulina; Husni Tamim; Prietia Eko Wardoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Self-regulated learning is the capacity of students to actively manage their own learning process through the stages of planning, performance, and reflection, which plays an important role in determining academic success and motor skill achievement. This study aims to examine the effect of implementing a peer coaching model on the improvement of self-regulated learning among students of SMK 3 Selong in Physical Education. A quantitative approach with a quasi-experimental pretest-posttest control group design was employed, involving 30 students divided into an experimental group (n=15) receiving the peer coaching model and a control group (n=15) following conventional instruction. The equivalence test confirmed that both groups were at a comparable baseline before the intervention (t=0.634; p=0.531). Following the intervention, the experimental group showed a larger increase in self-regulated learning score (gain=10.13) compared to the control group (gain=1.93), with an independent t-test revealing a significant difference (t=2.090; p=0.046) and a large effect size (Cohen's d=0.763). Phase-level analysis showed a consistent upward pattern on the performance and reflection phases, although the subscale-level differences did not reach statistical significance. Supporting observational data showed that the fidelity of peer coaching implementation increased from 77.78 percent in the first session to 91.27 percent in the fifth session, further triangulated by an increase in teacher-observed self-regulated learning behavior scores in the experimental group. These findings provide empirical evidence that the peer coaching model effectively improves the self-regulated learning of vocational high school students in Physical Education and is worth considering as an alternative teaching strategy.